2013
DOI: 10.1093/nar/gkt679
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Nop2 and Rcm1 methylate C2870 and C2278 of the 25S rRNA, respectively

Abstract: Yeast 25S rRNA was reported to contain a single cytosine methylation (m5C). In the present study using a combination of RP-HPLC, mung bean nuclease assay and rRNA mutagenesis, we discovered that instead of one, yeast contains two m5C residues at position 2278 and 2870. Furthermore, we identified and characterized two putative methyltransferases, Rcm1 and Nop2 to be responsible for these two cytosine methylations, respectively. Both proteins are highly conserved, which correlates with the presence of two m5C re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
210
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(219 citation statements)
references
References 51 publications
3
210
0
Order By: Relevance
“…In a recent report (Sharma et al 2013), polysome profiling of yeast lacking Rcm1p did not produce such an obvious "shoulder." However, Sharma et al (2013) used higher sucrose concentrations in their gradient centrifugation that probably resulted in a more compressed profile with such a shoulder far less obvious.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In a recent report (Sharma et al 2013), polysome profiling of yeast lacking Rcm1p did not produce such an obvious "shoulder." However, Sharma et al (2013) used higher sucrose concentrations in their gradient centrifugation that probably resulted in a more compressed profile with such a shoulder far less obvious.…”
Section: Discussionmentioning
confidence: 94%
“…We did not observe anisomycin sensitivity in our rcm1Δ strain. Interestingly, Sharma et al (2013) reported recently that yeast strains lacking Rcm1p were also anisomycin sensitive. This discrepancy could be due to different genetic backgrounds of the parental strains used in each study and/or different experimental setups used to assay the sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, it has been shown that m5C modification of tRNA plays an important role in tRNA stability and in the regulation of translational fidelity (Schaefer et al 2010;Tuorto et al 2012Tuorto et al , 2015. Furthermore, m5C is also a widely conserved modification of rRNA, where it is implied in the quality control of ribosome biogenesis (Sharma et al 2013;Bourgeois et al 2015;Schosserer et al 2015). These processes have been associated with a variety of human diseases (Blanco and Frye 2014).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%